Recognising the racial past and discriminatory present of international law – the international community’s response to the Russian invasion of Ukraine - Razzaki, Usaid Mutjaba (University of the Witswatersrand, Johannesburg, 2024)
On 24 February 2022, Russia unilaterally invaded Ukraine without any prior United Nations Security Council (‘UNSC’) approval. Within ten days of this invasion, the United Nations General Assembly (‘UNGA’) adopted resolution A/49/L.1 condemning Russia’s invasion of Ukraine and demanding the immediate removal of Russian troops from Ukrainian territory. Moreover, on 28 February 2022, only four days after the initial invasion, the International Criminal Court’s (‘ICC’) Chief Prosecutor Karim A. A. Khan of the United Kingdom decided to ‘open an investigation into the situation of Ukraine’. In the Middle East, territorial wars, or wars relating to borders have been fought between Palestine and Israel since 1948. There is evidence that an investigation was launched into the case of Palestine on 03 March 2021. But my criticism is this; whereas it took the ICC merely 4 days to launch such an investigation in Ukraine, it took the ICC nearly 70 years to do the same in Palestine. The UNSC is reduced to a council where political decisions are influenced based on gratuity of allies and own political agendas where the international law framework itself provides for a loophole for international law to be manipulated, construed, and controlled to the whims and fancies of the powerful (big 5) nations through the use of the veto power. Then, I argue, international law as it currently stands, is in need of serious remodelling.
Submitted in partial fulfilment of the requirements for the degree of Master of Laws by Coursework and Research Report at the University of the Witwatersrand, Johannesburg
Keywords: UCTD; United Nations Security Council (‘UNSC’); International Criminal Court’s (‘ICC’); Racial past; International law; Russian invasion of Ukrain; SDG-16: Peace, justice and strong institutions